Growing Public Concern Towards the Implementation of Inclusive Education - Rifqi Khairul Anam (Action Research Journal Indonesia (ARJI), 2024)
There are children in this world who have special needs and experience significant abnormalities or deviations in their physical, mental, intellectual, social, and emotional development compared to other children of the same age. As a result, they require special education services. Inclusive education is a specialized kind of education designed to cater to the unique requirements of children with special needs. The underlying principle of this educational concept is to shift the focus from adapting students to fit the requirements of the school, to instead adapting schools or educational systems to accommodate the needs of children. Researchers did community service by socializing education for children with special needs at the ABA 5 Probolinggo Kindergarten inclusive school. The focus of the community service was "Growing Community Awareness of the Implementation of Inclusive Education." The inclusive school employs Participatory Action Research to facilitate the socialization of education for students with special needs. This is achieved via many ways such as presentations, lectures, conversations, and hands-on activities. The primary outcome of this event is that inclusive education offers educational services that encompass the integration of children with special needs into regular courses, where they study alongside their peers of the same age. When society acknowledges the presence of children with special needs, it will become more feasible to establish an inclusive educational institution.